The Culture and Tradition of Educational Practice In Madrasah - Mantau, Burhanudin Abdul Karim; Buhungo, Ruwiah Abdullah (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This article aims to explore the tradition and culture of education in madrasahsMadrasah to see the educational construction found in the reinforcement of a nation’s character. This study used a qualitative approach of ethnography study, which emphasizes the importance of the central role of culture in understanding the way of life of observed groups through the ethnography method. Furthermore, the data source consists of primary data such as the words or spoken stuff and the behaviors from the subjects related to the Madrasah’s educational instruction in the reinforcement of characters and secondary data such as text, recording, or pictures, which is related to educational practices conducted. The findings show that the educational culture and tradition of the Madrasah have transformed the characters’ values scientifically through the tradition implemented in the daily activity of the people in the Madrasah. The uniqueness of characteristics of people in the Madrasah is shown through the individual or group behavior, language, and tradition, which can reflect the values of honesty, togetherness, tolerance, respect, and others, which all values are part of the substance in reinforcing characters. The reinforcement of students’ character at Madrasah is through the process of self-establishment, the habituation of good students’ behavior through every activity until they become strong cultural characters.